A Study on the Job Satisfaction of the Employees of Fireworks Industries - Chandra Bose, S.; Madasamy, V. (Prabandhan: Indian Journal of Management, 2009)
The happier people are within their job, the more satisfied they are said to be. Job satisfaction is not the same as motivation, although it is clearly linked. Job design aims to enhance job satisfaction and performance, methods include job rotation, job enlargement and job enrichment. Other influences on satisfaction include the management style and culture, employee involvement, incentives, empowerment and autonomous work groups. Job satisfaction is a very important attribute which is frequently measured by organizations. The most common way of measurement is the use of rating scales where employees report their reactions to their jobs. Questions relate to rate of pay, work responsibilities, variety of tasks, promotional opportunities the work itself and co-workers. In this regard, an attempt was made to study the job satisfaction of the workers of fireworks factories in Virudhunagar district. Three statistical tools were applied to study the level of job satisfaction of the workers. Findings show that job characteristics such as safety and welfare measures, incentives, promotional opportunity, task clarity and significance, transport facilities and skills utilization, as well as organizational characteristics such as commitment and relationship with supervisors and co-workers, have significant effects on job satisfaction. These job characteristics can be carefully managed to enhance job satisfaction. It has also been found that there is no significant relationship between income and overall job satisfaction of the respondents and there is no significant relationship between working conditions and overall job satisfaction of the respondents and the employees have medium level of satisfaction on their job.